PRINSIP MENGENAL NASABAH (KNOW YOUR CUSTOMER PRINCIPLE) DALAM PRAKTIK PERBANKAN - Rozali, Asep (Sekolah Tinggi Hukum Bandung, 2011)
The banking industry in its development in Indonesia is inseparable from the problems of the problem. The problems are caused by not understanding regulations in banking practices, such as regulation on Know Your Customer Principle.Know Your Customer Principle regulated in Bank Indonesia Regulation No. 5/23/PBI/Tahun 2003, dated October 23, 2003 is one attempt to realize the prudential principle which is a legal principle in the Banking Act. Thus, the importance of Know Your Customer Principle so that the application does not just apply nationally, but internationally as well. Even recommended by the Basel Committee on Banking Supervision, which is contained in the organizational committee of the Bank forÂ International Settlements.Know Your Customer Principle is not only related to âthe healthiestâ of a bank, but also beneficial to prevent the occurrence of suspicious transactions from customers that lead to the act of money laundering.Keywords: Legal Principle - Know Your Customer Principle - Principle of prudential